Non-adherence of WHO 2016 ANC model and associated factors among mothers who gave birh at conflict areas of south Gondar zone public hospitals - Begizew Yimenu Mekuriaw; Wassie Yazie Ferede; Fillorenes Ayalew Sisay; Besfat Berihun Erega; Assefa kebie Mitku; Tegegne Wale Belachew; Tigist Seid Yimer; Dagne addisu Sewyew; Habtie Bantider Wubet; Negesse Zurbachew Gobezie; Alemie Fentie Mebratie; Moges Kefale Alachew; et al. (Elsevier, 2024)
Background: In order to reduce stillbirth and perinatal mortality, world health organization recommended eight or more antenatal care contacts which is named as WHO 2016 ANC model recently. However, the effectiveness of the model depends on the adherence of pregnant mother and studies are absent as far as our search in Ethiopia. Therefore the aim of this study is to assess Non-adherence of WHO 2016 ANC model and associated factors among mothers who gave birth at south Gondar public hospitals. Methods: Multi-center crossectional study design was conducted among 412 postnatal and laboring mothers from September 01-November/30/2023. Participants were selected with systematic sampling technique. Interviewer administered questioner was used to collect the data. Factors associated with non-adherence of antenatal care were identified using bi-variable and multi variable logistic regression models. Statistical significance was defined at 95 %CI and p-value < 0.05. Result: In this study, 74.3 % (95 % CI: 70.03, 78.51) of respondents were non-adherence to WHO 2016 ANC model. Women who reside in rural areas (AOR=2.28, CI: 1.17-4.43), income generator being husband (AOR=2.43, CI: 1.1-5.5), husband decision on health care (AOR=6.24, CI: 2.94-13.25), unplanned pregnancy (AOR=2.9; CI: 1.47-5.71), Hours taken to reach health institution >2 hrs (AOR=4.84; CI: 2.33-10.06) and women who had poor knowledge on danger signs (AOR=3.29; CI: 1.49-7.26) were significantly associated with non-adherence of WHO 2016 ANC model. Conclusion: The magnitude of non-adherence to antenatal care contact is high. Accessing health facilities, empowering women, and educating them on danger signs are important.